Visual-Textual Prototyping of 4D Scenes - Dücker, M.; Geiger, Christian; Hunstock, R.; Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the 1997 IEEE Symposium on Visual Languages)
3D-graphics are becoming popular in a steadily increasing number of areas such as entertainment, scientific visualization, simulation, and virtual reality. Despite this rapid growth the generation of animated 3D scenes is by no means trivial. Since animated 3D objects evolve over time the authors denote these objects as 4D. The article presents a novel approach to the rapid prototyping of 4D models. They introduce the AAL (Animated Agent Layer) system. AAL is an interpreter-based approach covering a textual (AAL-PR) as well as a visual command language (AAL-VL) for the specification of the dynamics in 4D scenes. AAL provides support for different levels of abstraction: primitives, structured objects, animated objects, and animated (autonomous) agents.
Keywords: Prototypes; Layout; Animation; Command languages; Application software; Libraries; Virtual reality; Computer graphics; Hardware; Context modeling

A Generic System for Interactive Real--Time Animation - Dücker, M.; Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C. (Proceedings International Conference and Workshop on Engineering of Computer-Based Systems)
The authors present a new approach to an interactive design and analysis environment for visual languages. The main components, i.e., editor animator and interpreter are introduced. Their interactions are being investigated emphasizing the interpreter-animator interaction and defining an interface supporting different levels of automation. The interpreter performs the executions on a logical level and triggers the animator. The interactive animation provides a very high degree of liveness since it is based on the tight integration of the animator and editor. The proposed architecture permits the distributed implementation of a system for real-time animation. Their concepts are validated by the implementation of a debugging environment for the complete visual programming language Pictorial Janus.
Keywords: Real time systems; Animation; Debugging; Automation; Computer languages; Timing; Environmental management; Programming environments; Visualization; Multimedia systems

Bistable Diffractive Electro-Optical Effect in Cholesteric Gels* - Kitzerow, Heinz-Siegfried (Japanese Journal of Applied Physics)
The present study shows that a cholesteric gel consisting of a low molar mass liquid crystal and a highly crosslinked anisotropic network can be switched between a transparent and a colored scattering state. The latter state can be induced in an initially non-aligned cholesteric liquid crystal by an electric field, as described recently by Chilaya and coworkers. A short pulse of an electric field can be used to select between the two states which are stable at zero field. The angular dependence of the wavelength of the diffracted light is studied in detail and explained by the known properties of the spatially periodic cholesteric structure.
Keywords: General Physics and Astronomy; General Engineering

Transient Light Scattering of a Ferroelectric and an Antiferroelectric Liquid Crystal with Short Pitch - Kitzerow, Heinz-Siegfried (Japanese Journal of Applied Physics)
The electrooptic properties due to the transient light scattering mode (TSM) are studied for non-aligned ferroelectric and antiferro-electric liquid crystals with short pitch. The transient light scattering appears in thick samples without polarizers if the sign of an applied dc field is reversed. As a consequence, an ac field of suitable frequency can be used to switch the sample from a transparent to a scattering state. Due to the short pitch, a colored scattering can be observed under oblique angles. The latter effect provides high contrast ratios.
Keywords: General Physics and Astronomy; General Engineering

Azimuthal surface gliding of a nematic liquid crystal - Vorflusev, V. P.; Kitzerow, Heinz-Siegfried; Chigrinov, V. G. (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Azimuthal anchoring of liquid crystals at the surface of photo-induced anisotropic films - Vorflusev, V.P.; Kitzerow, Heinz-Siegfried; Chigrinov, V.G. (Applied Physics A: Materials Science & Processing)
Keywords: General Materials Science; General Chemistry

Influence of the Azimuthal Anchoring Energy on the Smectic Layer Formation in Ferroelectric Liquid Crystals - Vorflusev, Valery P.; Kitzerow, Heinz-Siegfried (Molecular Crystals and Liquid Crystals Science and Technology. Section A. Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics

Polymer-Dispersed Chiral Discotic Liquid Crystals - Kitzerow, Heinz-Siegfried; Bock, H. (Molecular Crystals and Liquid Crystals Science and Technology. Section A. Molecular Crystals and Liquid Crystals)
Keywords: Condensed Matter Physics

An Uncertainty Principle for Ultraspherical Expansions - Rösler, Margit; Voit, Michael (Journal of Mathematical Analysis and Applications)
Keywords: Applied Mathematics; Analysis

KANT V4 - DABERKOW, M.; FIEKER, C.; Klüners, Jürgen; POHST, M.; ROEGNER, K.; SCHÖRNIG, M.; WILDANGER, K. (Journal of Symbolic Computation)
The software packageKANT V4for computations in algebraic number fields is now available in version 4. In addition a new user interface has been released. We will outline the features of this new software package.
Keywords: Computational Mathematics; Algebra and Number Theory

On Computing Subfields - Klüners, Jürgen; Pohst, Michael (Journal of Symbolic Computation)
The purpose of this article is to determine all subfields ℚ(β) of fixed degree of a given algebraic number field ℚ(α). It is convenient to describe each subfield by a pair (h,g) of polynomials in ℚ[t] resp. Z[t] such thatgis the minimal polynomial of β = h(α). The computations are done in unramifiedp-adic extensions and use information concerning subgroups of the Galois group of the normal closure of ℚ(α) obtained from the van der Waerden criterion.
Keywords: Computational Mathematics; Algebra and Number Theory

Über die Berechnung von Automorphismen und Teilkörpern algebraischer Zahlkörper (Dissertation) - Klüners, Jürgen

CMOS-compatible organic light-emitting diodes - Heinrich, L.M.H.; Muller, J.; Hilleringmann, Ulrich; Goser, K.F.; Holmes, A.; Hwang, Do-Hoon; Stern, R. (IEEE Transactions on Electron Devices)

Polarons, localization, and excitonic coherence in superradiance of biological antenna complexes - Meier, Torsten; Zhao, Y.; Chernyak, V.; Mukamel, S. (The Journal of chemical physics)
A real-space formulation of time-resolved fluorescence of molecular aggregates is developed using the one-exciton density matrix ρ(t) of the optically driven system. A direct relationship is established between the superradiance enhancement factor Ls and the exciton coherence size Lρ associated with the off-diagonal density matrix elements in the molecular representation. Various factors which affect the latter, including finite temperature, energetic disorder, coupling with phonons, and polaron formation are explored. The theory is applied for the interpretation of recent measurements in the B850 system of the LH2 photosynthetic complexes.

Microscopic theory of the intracollisional field effect in semiconductor superlattices - Meier, Torsten; Hader, J.; Koch, M.; Rossi, F.; Linder, N. (Physical Review B)
A detailed analysis of the optical and transport properties of semiconductor superlattices in the high-field regime is presented. Electronic Bloch oscillations and the resulting terahertz emission signals are computed including phonon damping in the presence of the electric field. The modifications of the phonon-induced terahertz signal decay are analyzed including the movement of the carriers in the field (intracollisional field effect). For elevated fields it is shown that the interplay between electric field and electron-phonon interaction leads to resonance structures in the terahertz damping rate.

Femtosecond Photon Echoes in Molecular Aggregates - Meier, Torsten; Chernyak, V.; Mukamel, S. (The Journal of chemical physics)
Two-pulse four-wave-mixing signals from molecular aggregates, including effects of two-exciton states, static disorder, and exciton-phonon interaction represented by arbitrary spectral densities are calculated. Three types of contributions to the signal are identified. The first, reflecting exciton self-correlation, is similar to the photon echo from disordered two-level systems and dominates the signal for long time-delays. The second is related to correlations of one-exciton states, whereas the third reflects correlations between one- and two-exciton states. The information gained by completely resolving the signal field (both amplitude and phase) is analyzed using Wigner spectrograms.

Rückmeldung zu den Pfingstpredigten - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

Predigt: Die vielen Glieder (1 Kor 12,12-27) - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

Predigt mit Gesten zur ersten Vaterunser-Bitte - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

Density-Matrix-Electronic-Oscillator Representation of Optical Spectroscopy of Semiconductor Nanocrystals - Meier, Torsten; Yokojima, S.; Mukamel, S. (The Journal of chemical physics)
The optical response of CdSe semiconductor nanocrystals is investigated using the reduced single-electron density matrix in real space, calculated by means of the time-dependent Hartree–Fock technique. The spectroscopic signatures of exciton confinement are analyzed using the frequency-dependent electronic coherence matrix (off-diagonal density-matrix elements). The effects of Hartree and the Fock (exchange) type Coulomb interactions on the exciton binding energy are discussed. The latter result in almost dark excitons situated energetically below the main transition. Off-diagonal Coulomb matrix elements lead to larger exciton binding energies compared with previous calculations, and result in a better agreement of the size dependence of the lowest optical transition with experiment.